TRAUMA MEDULA SPINALIS - Reno Sari Caniago; Yulson, Yulson (Yayasan Nusantara Hasana Berdikari, 2025)
Spinal cord injury (SCI) is a neurological emergency caused by mechanical trauma to the spinal cord, resulting in impaired sensory, motor, and autonomic functions below the level of the lesion. This condition commonly occurs due to blunt trauma, motor vehicle accidents, falls from height, or penetrating injuries. The pathophysiology of SCI involves a primary injury, such as contusion or compression of the spinal cord, followed by secondary injury processes leading to progressive edema, inflammation, and ischemia. Rapid and appropriate management is crucial to minimize permanent damage, including early stabilization, spinal immobilization, neurological assessment, and diagnostic imaging. Definitive treatment may include surgical decompression, spinal stabilization, management of complications, and long-term rehabilitation. SCI has a significant impact on patients’ quality of life and requires a multidisciplinary approach to achieve optimal functional outcomes.